2020
DOI: 10.1016/j.disc.2019.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Fuglede’s conjecture fails in 4 dimensions over odd prime fields

Abstract: We describe computer programs accompanying our paper [3] and show that running them suffices to verify Fuglede's conjecture in Z 5 2 and Z 6 2 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…However, this exception seems to be due to the small number of points and is not an indication for larger dimensions. These results were found independently and with different methods by Ferguson and Sothanaphan [6].…”
Section: Spectral Setsmentioning
confidence: 64%
“…However, this exception seems to be due to the small number of points and is not an indication for larger dimensions. These results were found independently and with different methods by Ferguson and Sothanaphan [6].…”
Section: Spectral Setsmentioning
confidence: 64%
“…It was proved in [10] that for Z 2 p Fuglede's conjecture holds for every prime p. On the other hand, it was shown in [1] that the spectral tile direction of the conjecture does not hold for Z 5 p if p is an odd prime and for Z 4 p if p ≡ 3 (mod 4) is a prime. This was strengthened by Ferguson and Sothanaphan by exhibiting a non-spectral tile for Z 4 p , see [7]. If p = 2, then the situation is slightly different.…”
Section: Introductionmentioning
confidence: 92%
“…If p = 2, then the situation is slightly different. It was shown that Fuglede's conjecture fails for Z d 2 if d ≥ 10 [7], and holds if d ≤ 6 [7,8]. For 7 ≤ d ≤ 9 the answer is not known.…”
Section: Introductionmentioning
confidence: 99%
“…We return to the setting of this paper, namely finite Abelian groups: for finite Abelian groups with two generators, it has been shown that Fuglede's conjecture holds in Z p × Z p [11], a result later extended to Z p × Z p 2 [28]. When the generators are at least four, the Spectral⇒Tiling direction fails when the cardinality of the group is odd [8].…”
Section: Introductionmentioning
confidence: 99%